TAUBERIAN THEOREM FOR GENERAL MATRIX SUMMABILITY METHOD - Bidu Bhusan Jena; Priyadarsini Parida; Susanta Kumar Paikray (Ural Mathematical Journal)
In this paper, we prove certain Littlewood–Tauberian theorems for general matrix summability method by imposing the Tauberian conditions such as slow oscillation of usual as well as matrix generated sequence, and the De la Vallée Poussin means of real sequences. Moreover, we demonstrate \((\bar{N},p_{n})\) and \((C,1)\) – summability methods as the generalizations of our proposed general matrix method and establish an equivalence relation connecting them. Finally, we draw several remarks in view of the generalizations of some existing well-known results based on our results.